IgE binding to linear epitopes of Ara h 2 in peanut allergic preschool children undergoing oral Immunotherapy. Issue 8 (21st October 2019) - Dreskin, Stephen C.; Germinaro, Matthew; Reinhold, Dominik; Chen, Xueni; Vickery, Brian P.; Kulis, Michael; Burks, A. Wesley; Negi, Surendra S.; Braun, Werner; Chambliss, Jeffery M.; Eglite, Spodra; McNulty, Caitlin M. G.
Abstract: Background: For patients with peanut allergy, there are currently no methods to predict who will develop sustained unresponsiveness (SU) after oral immunotherapy (OIT). Objective: Assess IgE binding to peanut (PN), Ara h 2, and specific linear epitopes of Ara h 2 as predictors of the important clinical parameters: eliciting dose threshold and attainment of SU following OIT. Methods: Samples and clinical data were collected from children undergoing OIT. PN‐ and Ara h 2‐sIgE were quantified by ImmunoCAP ® . IgE binding to linear peptides of Ara h 2 and Ara h 6 was measured with peptide microarrays. Results: Values of PN‐sIgE correlated with eliciting dose ( P = .001) and with a higher likelihood of achieving SU ( P < .0001), but these relationships were lost at higher values for PN‐sIgE (≥14 kIU for eliciting dose and ≥35 kIU/L for SU). In subjects with PN‐sIgE ≥ 14 kIU/L, binding of IgE to epitopes 5 and 6 of Ara h 2 was associated with a lower eliciting dose at baseline challenge ( P < .001; P c < .02). In subjects with PN‐sIgE ≥ 35 kIU/L, a combined model of IgE binding to epitopes 1, 5 and 6 with PN‐sIgE was highly predictive of attainment of SU (AUC of 0.86; P = .0067). Conclusion: In young patients with peanut allergy, measurement of PN‐sIgE and IgE binding to specific linear epitopes of Ara h 2 in baseline samples may allow stratification of patients regarding sensitivity to challenge and outcome of OIT. Abstract :